2016
DOI: 10.1159/000450785
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Publication Rate of the Abstracts Presented at a National Gastroenterology Meeting after 6 Years

Abstract: Background/Aims: Abstract presentations at scientific meetings provide an opportunity to communicate the results of important research. Unfortunately, many abstracts are not published as full manuscripts. At the 73rd scientific meeting of the American College of Gastroenterology in 2008, we evaluated factors associated with the publication of abstracts as manuscripts up to 6.5 years after presentation. Methods: All abstracts, excluding case reports, presented at the meeting were evaluated. We systematically se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 8 publications
(12 reference statements)
0
5
0
1
Order By: Relevance
“…Given that author origin (from non-English-language countries vs. from English-language countries) might affect the abstract publication rate [ 4 , 9 , 15 ], our findings might be limited to Japan and might not be generalizable to authors originating from English-language countries. However, a past systematic review reported an effect of specialties on the publication rate of abstracts [ 16 ]. Therefore, it is unclear whether the lower publication rate observed in this study is attributable to the country (Japan), the specialty (geriatrics), or other factors.…”
Section: Main Textmentioning
confidence: 99%
“…Given that author origin (from non-English-language countries vs. from English-language countries) might affect the abstract publication rate [ 4 , 9 , 15 ], our findings might be limited to Japan and might not be generalizable to authors originating from English-language countries. However, a past systematic review reported an effect of specialties on the publication rate of abstracts [ 16 ]. Therefore, it is unclear whether the lower publication rate observed in this study is attributable to the country (Japan), the specialty (geriatrics), or other factors.…”
Section: Main Textmentioning
confidence: 99%
“…While abstract publications provided limited data for research activity in a specific field of research, there is some evidence of relatively poor rates for conversion to publications, 15 , 16 …”
Section: Discussionmentioning
confidence: 99%
“…The publication rate of manuscripts resulting from oral plenary session abstracts from 2006 to 2016 at the SGO annual meeting was 85.8%. Publication rates at the meetings of other medical societies varied widely; American College of Gastroenterology’s (ACG) annual meeting, for instance, had a publication rate of 55.6% for oral presentations, and the Canadian Association of Radiologists saw only 28% of abstracts advanced to publication ( Gandhi et al, 2016 , Dressler and Leswick, 2015 ). At other subspecialty society meetings, however, a higher percentage of oral plenaries advanced to publication ( Cheng et al, 2017 , Bowers et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%